Great Expectations and Mismatched Compensation: Government Sponsored Public Participation in Proceedings of the Consumer Product Safety Commission - Carl Tobias (Washington University Law Quarterly, 1986)
The initial section of this Article describes the origins and development of participant funding, focusing on the Consumer Product Safety Commission's institution and implementation of the compensation concept. The second part of the Article assesses the quality, and the impact on administrative decision-making, of the reimbursed public involvement that occurred at the Commission. The third portion draws conclusions about funded activity in agency matters from the CPSC's experience, and the final section offers suggestions for future experimentation.
Keywords: Government agencies; Political participation; U.S. Consumer Product Safety Commission